Small fixed fire extinguishers Part 1. Specification for small fixed halon fire extinguishers (BSI, 1990)
Fire extinguishers (built-in), Fire extinguishers, Firefighting equipment, Halogenated hydrocarbons, Small, Mass, Filling, Density, Performance, Closures, Installation, Marking, Sampling methods, Corrosion tests, Pressure testing, Internal pressure, Leak tests, Flow rates, Flow measurement